1997
DOI: 10.1002/(sici)1097-010x(19970401)277:5<390::aid-jez5>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the ability of precursor germ cells and epididymal spermatozoa to generate reactive oxygen metabolites

Abstract: Male germ cells at various stages of differentiation from pachytene spermatocytes to mature caudal epididymal spermatozoa were examined for their ability to generate reactive oxygen species (ROS) using sensitive chemiluminescence techniques. In general, spermatozoa were found to spontaneously generate hydrogen peroxide as they progressed through the epididymis, maximal activity being observed on the release of mature cells from the caudal region into a modified Krebs‐Ringer's solution. The spontaneous producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(67 citation statements)
references
References 48 publications
2
65
0
Order By: Relevance
“…The effects of oxidative stress on the genomic integrity of spermatozoa have been studied by inducing oxidative stress in the testis and in mature spermatozoa (Aitken et al 1989, Lucesoli & Fraga 1995. Within the testis a number of cell types produce high levels of reactive oxygen species (ROS) that may result in oxidative damage to DNA, proteins and cell membranes and to combat this, the testis has developed a very complex antioxidant system (Bauche et al 1994, Fisher & Aitken 1997. Therefore decreased expression of oxidative stress response genes, including extracellular superoxide dismutase (SOD) 3, manganese SOD 2 and genes involved in the metabolism of glutathione, which has been reported to occur following heating, may leave cells more susceptible to oxidative DNA damage (Barroso et al 2000, Rockett et al 2001 A number of DNA repair mechanisms have been documented to be active during spermatogenesis (Richardson et al 2000, Aguilar-Mahecha et al 2001, Aitken & Krausz 2001, Rockett et al 2001, Hsai et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of oxidative stress on the genomic integrity of spermatozoa have been studied by inducing oxidative stress in the testis and in mature spermatozoa (Aitken et al 1989, Lucesoli & Fraga 1995. Within the testis a number of cell types produce high levels of reactive oxygen species (ROS) that may result in oxidative damage to DNA, proteins and cell membranes and to combat this, the testis has developed a very complex antioxidant system (Bauche et al 1994, Fisher & Aitken 1997. Therefore decreased expression of oxidative stress response genes, including extracellular superoxide dismutase (SOD) 3, manganese SOD 2 and genes involved in the metabolism of glutathione, which has been reported to occur following heating, may leave cells more susceptible to oxidative DNA damage (Barroso et al 2000, Rockett et al 2001 A number of DNA repair mechanisms have been documented to be active during spermatogenesis (Richardson et al 2000, Aguilar-Mahecha et al 2001, Aitken & Krausz 2001, Rockett et al 2001, Hsai et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…We have established previously that oxidative stress is capable of inducing the ␤-pol-mediated BER pathway in various tissues (52). Furthermore, in response to an active state of spermatogenesis, there is a constant level of oxidative stress in testes (62,63), and unrepaired oxidative damage has been shown to induce abnormal sperm with reduced fertility (64). However, recent reports (65) have indicated that nuclear DNA of human spermatozoa is relatively resistant to damage induced by H 2 O 2 and iron treatment in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the impact of ROS on male fertility is a question of degree rather than the presence or absence of the pathology. A study by Fisher and Aitken (26) has indicated that male germ cells at various stages of differentiation from pachytene spermatocytes to mature caudal epididymal spermatozoa from mature male rats, mice, hamsters, and guinea pigs have the potential to generate ROS. Clear evidence also suggests that human sperm can produce ROS (27,28).…”
Section: Reactive Oxygen Species and Male Infertilitymentioning
confidence: 99%